Does avatar's character and emotional bond expose to gaming addiction? Two studies on virtual self-discrepancy, avatar identification and gaming addiction in massively multiplayer online role-playing game players. (March 2019) - Mancini, Tiziana; Imperato, Chiara; Sibilla, Federica
Abstract: This study aims to analyze virtual self-discrepancy (VSD), avatar identification, and gaming addiction in Massively Multiplayer Online Role-Playing Games (MMORPGs). Two studies were conducted to test the relations between VSDs (i.e., idealized vs utopian avatar), avatar identification, and gaming addiction. In the cross-sectional survey (Study 1; 770 MMORPGs players) we assumed that higher MMORPG addiction was directly predicted by the construction of an idealized avatar (vs. utopian avatar) and by the avatar identification, which also mediated the relationship between the VSDs and gaming addiction. In the 2 × 2 experimental study (Study 2; 100 participants), manipulating VSD and avatar identification, we assumed that MMORPG addiction risk was higher in the idealized avatar-high identification condition than in the utopian avatar-low identification condition. Results confirmed that the more idealized the avatar was, the more the users increased their avatar identification (Study 1), that in turn was associated with gaming addiction (Study 1 and Study 2), and that only an idealized avatar (vs. utopian avatar) directly affected gaming addiction (Study 1). Furthermore, results showed that MMORPG addiction risk was higher in participants who customized an idealized avatar and identified with it (vs. utopian avatar-low identification) (Study 2). Highlights: Avatar identification increases addiction risk more than avatar customization. Creating an idealized avatar increases identification with it. Using an idealized avatar is riskier than using a utopian avatar. The risk of addiction can be avoided by keeping a low identification with the avatar.